2020
DOI: 10.1016/j.celrep.2020.107679
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Lymph Node Niches Enhances Type 1 Immune Responses to Immunization

Abstract: SUMMARY Generating robust CD4 + T-helper cell type 1 (Th1) responses is essential for protective vaccine-induced type 1 immunity. Here, we examine whether immunization formulation associated with enhanced vaccine efficacy promotes antigen targeting and cell recruitment into lymph node (LN) niches associated with optimal type 1 responses. Immunization with antigen and Toll-like receptor agonist emulsified in oil leads to an increased differentiation of IFNγ/TNF-α + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…A study of incomplete Freund’s adjuvant (IFA) containing mineral oil and surfactant similarly favored the use of adjuvanted vaccine and indicated that an oil formulation may further enhance efficacy ( Lian et al, 2020 ). The oil emulsion in IFA-containing immunizations better distributed both ovalbumin (antigen) and lipopolysaccharide (adjuvant), causing stronger Th1 differentiation in response to vaccination.…”
Section: Therapeutics and Vaccinesmentioning
confidence: 99%
“…A study of incomplete Freund’s adjuvant (IFA) containing mineral oil and surfactant similarly favored the use of adjuvanted vaccine and indicated that an oil formulation may further enhance efficacy ( Lian et al, 2020 ). The oil emulsion in IFA-containing immunizations better distributed both ovalbumin (antigen) and lipopolysaccharide (adjuvant), causing stronger Th1 differentiation in response to vaccination.…”
Section: Therapeutics and Vaccinesmentioning
confidence: 99%
“…The specific transcriptional program of T H1 or T SLEC effectors, T FH, and T SCM cells moves cells into spatially distinct regions of draining lymph nodes viral infection or by using specific vaccination strategies that target antigen to this region. 1,136,137 Using a dual CXCR3 ligand reporter mouse, we demonstrated that CXCR3+ CD4+ T cell movement is directed by the expression of CXCL9 and CXCL10 in this region. 7 While this study did not reveal the precise dendritic cell or stromal cell population that move T cells into this area, we have now demonstrated that type 2 conventional dendritic cells (cDC2) express high levels CXCL10 in the IFR.…”
Section: F I G U R Ementioning
confidence: 95%
“…This has recently been investigated for the promotion of T H1 cell differentiation in vivo. 137 This study compared soluble Toll-like receptor and antigen delivered in the mineral oil emulsion, incomplete Freund's adjuvant (IFA). The use of the oil emulsion formulation altered the antigen deposition, moving it to the IFRs, rather than the medulla of draining lymph nodes.…”
Section: Some New Vaccination Methods May Influence the Location Of Tmentioning
confidence: 99%
See 2 more Smart Citations